Comparative Study on Tuberculosis Drug Resistance and Molecular Detection Methods Among Different Mycobacterium Tuberculosis Lineages - He CJ; Wan JL; Luo SF; Guo RJ; Paerhati P; Cheng X; Duan CH; Xu AM (Infection and Drug Resistance, 2023)
Chuan-Jiang He,1,2 Jiang-Li Wan,2 Sheng-Fang Luo,2 Rui-Jie Guo,2 Pawuziye Paerhati,2 Xiang Cheng,2 Chao-Hui Duan,1,* Ai-Min Xu2,* 1Department of Laboratory Medicine, Sun Yat-Sen Memorial Hospital, Sun Yat-Sen University, Guangzhou, 510120, People’s Republic of China; 2Department of Laboratory Medicine, The First People’s Hospital of Kashgar, Kashgar, 844000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ai-Min Xu, The First People’s Hospital of Kashgar, No. 66, Yingbin Avenue, Kashgar, Xinjiang, 844000, People’s Republic of China, Tel +86 0998-2970071, Email xuaimin2022@163.comPurpose: This study aims to compare drug resistance and detection efficacy across different Mycobacterium tuberculosis lineages, offering insights for precise treatment and molecular diagnosis.Methods: 161 strains of Mycobacterium tuberculosis (M.tb) were tested for drug resistance using Phenotypic Drug Susceptibility Testing (pDST), High-Resolution Melting analysis (HRM), and Whole Genome Sequencing (WGS) methods. The main focus was on evaluating the accuracy of different methods for detecting resistance to rifampicin (RIF), isoniazid (INH), and streptomycin (SM).Results: Among the 161 strains of M.tb, 83.85% (135/161) were fully sensitive to RIF, INH, and SM according to pDST, and the rate of multidrug resistance was 4.35% (7/161). The drug resistance rates of lineage 2 M.tb to the three drugs (26/219, 11.87%) were significantly higher than those of non-lineage 2 M.tb (12/264, 4.45%) (P< 0.05). Compared with pDST, WGS had a sensitivity of 100%, 94.12%, and 92.31% and a specificity of 100%, 99.31%, and 98.65% for RIF, INH, and SM, respectively, with no significant difference. The sensitivity of HRM for RIF, INH, and SM was 87.50%, 52.94%, and 76.92%, respectively, while the specificity was 96.08%, 99.31%, and 99.32%, respectively. The sensitivity of HRM for detecting INH resistance was significantly lower than that of pDST (P=0.039). Compared with HRM, WGS increased the sensitivity of RIF, INH, and SM by 12.50%, 41.18%, and 15.38%, respectively.Conclusion: There are significant differences in drug resistance rates among different lineages of M.tb, with lineage 2 having higher rates of RIF, INH, and SM resistance than lineages 3 and 4. The sensitivity of HRM is far lower than that of pDST, and currently, the accuracy of HRM is not sufficient to replace pDST. WGS has no significant difference in detecting drug resistance compared with pDST but can identify new anti-tuberculosis drug-resistant mutations, providing effective guidance for clinical decision-making.Keywords: Mycobacterium tuberculosis, whole-genome sequencing, lineage, drug resistance, sensitivity, specificity